Peningkatan Kemampuan Menulis Narasi Ekspositoris Berbantuan Mind Mapping Siswa Kelas VII.2 SMPN 2 Kamang Magek Kabupaten Agam - Hidayati, Vinazullah; R., Syahrul; Ratna, Ellya (Universitas Negeri Padang, 2012)
The purpose of this article is to explain the process and the improvement of learning outcomes narrative expository writing skills aided mind mapping class VII. 2 SMP Negeri 2 Kamang Magek that is viewed from four expository narrative writing assessment indicators, namely expanding knowledge, convey an event in chronological order, reasoning, and use language that is informative. Based on the research’s results it can be concluded that the application of mind mapping can improve the process and learning outcomes narrative expository writing skills of students of class VII. 2 SMP Negeri 2 Kamang Magek Agam District. It can be seen in the significant average of mark. In preliminary observations (pre-cycle) the average is 50,79% then in first cycle is 67,46%, the second cycle is 90,48%.